The Hazards of Malnutrition in Early Infancy - Ratna Indrawati (Indonesian Pediatric Society, 1976)
Severe protein calorie malnutrition is often accompanied by vitamin A deficiency and intercurrent infections. These three conditions have a synergistic action on each other. The younger the infant, the more severe are the hazards of nutritional deficiency. Severe malnutrition in early infancy results in: Direct hazards to the infant consisting of: Retardation of physical development. Retardation of brain development with subsequent impairment of learning ability. Decreased resistance against infections. PCM is a predisposing factor to diarrhoea, with aggravated the malnutrition. Blindness due to vitamin A deficiency.